167 Reflex methylation testing in endometrial cancer: a single centre retrospective study. (13th November 2020) - Honner, M; Siddique, N; McBain, R; Chan, F; McNally, O
Abstract : Introduction: Looking for evidence of microsatelite instablity (MSI) through immunohistochemistry (IHC) for loss of staining for mismatch repair (MMR) proteins MLH1, PMS2, MSH2 and MSH6 at the time of histopathological examination of endometrial cancers is increasingly becoming standard of care; to guide recurrent disease treatment and identify patients whose cancers may be the result of a genetic mutation eg. Lynch syndrome. Identification of IHC as a surrogate for MSI is employed in many centres. Currently patients need referral to a Familial Cancer Centre (FCC) for counselling prior to further tumour testing including methylation testing, which is more likely to be responsible for loss of staining for MLH1 and PMS2. Aim: Audit the practice of IHC for MMR proteins and identify efficiencies to the FCC referral pathway using reflex methylation testing. Methods: Patients diagnosed with endometrial cancer over a five-year period were included. Data was retrieved from the in-house clinical database, FCC database and patient histories and included: completeness of IHC for MMR, type of MMR loss of expression, proportion of referrals to FCC, number of genetic mutations identified, proportion of MLH1 and PMS2 as result of methylation. Results: Loss of staining for MMR was found in 20% of endometrial cancers. This was for MSH2/MSH6 in 1.7% and 19% for MLH1/PMS2. 95% of cases with loss of MMR proteins MLH1/PMS2 were found to be due to methylation and <5% had a germline mutation. 60% had a germline mutation in MSH2/MSH6. Conclusion: IHC for MMR at the time of endometrial cancer diagnosis is increasingly practiced. This study highlights the importance of reflex methylation testing in cases of MLH1 and PMS2 thus reducing the burden on patients and FCCs where hitherto methylation testing is not ordered before referral.